Promotion of liberal values in South African foreign policy : beyond the structural imperatives of the international system? - Mkalipi, Zanethemba (Rhodes University, Faculty of Humanities, Department of Political Studies, 2002)
The end of the Cold War in the early 1990s led to a multilateral international system no longer divided by contending forces of capitalism and communism. In the context of South Africa, the end of the Cold War occurred at a juncture where the apartheid government was being challenged by pro-democracy forces that have fought against it for decades. The developments in the international system and in the country led to South Africa adopting universal liberal values not only in its constitution, but also in its international relations. Foreign policy documents and statements by the ministry of Foreign Affairs also reflected the country's aspiration of becoming a mediator, a facilitator for democracy and a peacemaker especially in the context of Africa. International expectation mounted as South Africa was perceived as possessing the capacity to act in a manner that advances democratic values and which gives voice to the weak nations of the world. However, the aura of a post-apartheid South Africa that would act not only in its interest, but also in the interest of the world community never fully materialised. South Africa failed to act in a manner consistent with its stated commitment to democratic values when it recognised Peoples Republic of China, an undemocratic and repressive government. It also marched into Lesotho in 1998, resulting in the destabilisation of this tiny Southern African country. These events led to an increasing criticism of the South African government. Some argued that South Africa was still inexperienced given its recent emergence as a world player. Others blamed the inconsistency on a too broad and ambitious foreign policy that set itself for failure. This study seeks to contribute to the conceptual understanding of the debate regarding the ambiguous nature of South Africa's foreign policy behaviour. It situates the conceptualisation of South Africa's foreign policy within the predominant debates in international relations between realism, political structuralism and pluralism. Firstly, it holds that the end of the Cold War and ascendancy of globalist conceptions of international relations did not lead to the inadequacy of political structuralism as an organising framework. Secondly, it attempts to clarify the gap between South Africa's foreign policy and foreign policy behaviour by employing the assumptions advanced by political structuralism, Thirdly, a case study of South Africa's foreign policy towards China, Lesotho, the Great Lakes and Swaziland is carried out. Here it is demonstrated that the ambiguities of South Africa's foreign policy are a function of the constraints imposed by the political and economic structure of the international system, It draws its conclusion by providing methodological recommendations to South Africa's foreign policy makers and future researchers in the field of foreign policy analysis.
Keywords: South Africa -- Foreign relations